Activity pattern of free-living Ansell´s mole-rat (Fukomys anselli) as revealed by automatic radio-telemetry - Hausteinová, Tereza (Jihočeská univerzita, 2018)
Social behavior of some species of African mole-rats makes them interesting object of study. Members of multigenerational families were only one pair breeds collectively work on building of their burrow system and obtaining food. Distribution of activity during the day in individual family members may give us a clue of how they manage their work. However, studies monitoring mole-rats in their natural environment are scarce and usually carried out on low number of individuals. Present study deals with outside-nest activity of 16 free-living Ansell´s mole-rats using data obtained by automatic radio-telemetry - method which was used in radio-tracking of mole-rats for the first time. It reveals differences in activity pattern of individual mole-rats and examines how they relate to body mass, sex, reproductive status and affiliation to a family and test whether individuals of the same family tend to be synchronized in their outside nest activity.
Activity pattern of free-living Ansell´s mole-rat (Fukomys anselli) as revealed by automatic radio-telemetry
Keywords: Ansell´s mole-rat; activity pattern; synchronization; Ansell´s mole-rat; activity pattern; synchronization